PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA, DAN GAYA KEPEMIMPINAN TRANSFORMASI TERHADAP KINERJA KARYAWAN PADA PT.POS INDONESIA (PERSERO) KANTOR CABANG SITUBONDO 68300 DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Maulidiyah, Indana Yuris; Fandiyanto, Randika; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2025)
Human resources represent a critical element in supporting organizations to achieve their vision, mission, and carry out various operational activities. Moreover, human resources play a pivotal role in determining the success or failure of an institution in reaching its established goals. This study aims to evaluate and examine the extent to which organizational culture, work motivation, and transformational leadership style influence employee performance, with job satisfaction serving as a mediating variable at PT. Pos Indonesia, Situbondo Branch Office 68300, by employing Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the direct effect hypothesis testing using SmartPLS 3.0 indicate that organizational culture does not have a significant effect on job satisfaction. In contrast, work motivation demonstrates a significant positive effect on job satisfaction, while transformational leadership style shows a positive but not significant effect. Additionally, organizational culture exhibits a negative but not significant effect on employee performance. Meanwhile, work motivation has a significant positive effect on employee performance, and transformational leadership style has a positive but not significant effect on employee performance. The results of the indirect effect hypothesis testing reveal that organizational culture has a negative but not significant effect on job satisfaction through employee performance. Similarly, work motivation has a positive but insignificant indirect effect on job satisfaction through employee performance. Transformational leadership style also displays a positive but insignificant indirect effect on job satisfaction through employee performance.